2008
DOI: 10.1007/s00127-008-0481-3
|View full text |Cite
|
Sign up to set email alerts
|

Health service staff’s attitudes towards patients with mental illness

Abstract: The results indicate the need to develop sensitisation and training programs considering mental health topics among health service employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
5
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 32 publications
9
113
5
12
Order By: Relevance
“…Although, sociodemographic characteristics such as age, gender, marital status, education level have been reported in the literature to be effective in stigmatizing attitudes (8,24,27,30), in our sample sociodemographic characteristics were not effective on stigmatizing attitudes. It has also been reported that having contact with individuals with mental illness has a positive effect on stigmatizing attitudes (31).…”
Section: Discussioncontrasting
confidence: 78%
“…Although, sociodemographic characteristics such as age, gender, marital status, education level have been reported in the literature to be effective in stigmatizing attitudes (8,24,27,30), in our sample sociodemographic characteristics were not effective on stigmatizing attitudes. It has also been reported that having contact with individuals with mental illness has a positive effect on stigmatizing attitudes (31).…”
Section: Discussioncontrasting
confidence: 78%
“…Um estudo (8) feito na Grécia com 239 estudantes de medicina e 361 funcionários diversos constatou que os profissionais da ala psiquiátri-ca tiveram atitudes mais positivas em relação a pacientes com doença mental. Os autores concluíram que o contato com pacientes portadores de doença mental e a formação são importantes na redução do estigma entre o pessoal de saúde mental e de outros setores.…”
Section: Introductionunclassified
“…Research indicates that the more contact and familiarity there is with people with mental disorders, the lower the prejudice tends to be (Angermeyer & Matschinger, 2004;Arvaniti, Samakouri, Kalamara, Bochtsou, & Livaditis, 2009;Corrigan, Edwards, Qreen, Thwart, & Perm, 2001). Sousa, P. F., Maciel, S. C., Medeiros, K. T.…”
mentioning
confidence: 99%